1985
DOI: 10.2172/5659949
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of enriched uranium and uranium-aluminum fuel materials with the AWCC

Abstract: T he active well coincidence counter (AWCC) was calibrated at the Chalk River Nuclear Laboratories (CRNL) for the assay of 93%-enriched fuel materials in three categories: (1) uranium-aluminum billets, (2) uranium-aluminum fuel elements, and (3) uranium metal pieces. The AWCC was a standard instrument supplied to the International Atomic Energy Agency under the International Safeguards Project Office Task A.51. Excellent agreement was obtained between the CRNL measurements and previous Los Alamos National Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The AWCC was tested and used in different applications by many authors [7][8][9][10][11][12][13][14][15][16][17]. It was compared with other neutron coincidence detectors to investigate its precision, counting rate, accuracy, stability, and the effect of sample inhomogeneity [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AWCC was tested and used in different applications by many authors [7][8][9][10][11][12][13][14][15][16][17]. It was compared with other neutron coincidence detectors to investigate its precision, counting rate, accuracy, stability, and the effect of sample inhomogeneity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Menlove and Bosler [9] showed that the instrument could be used for assaying wide range of HEU samples in form of stacked disks to simulate buttons and thin metal plates both in thermal and fast modes taking into consideration the neutron self-shielding and multiplication. The AWCC was also calibrated [10] for assaying 93%-enriched fuel materials in different categories. Evaluation of the AWCC for field tests was performed by Krick and Rinard [11].…”
Section: Introductionmentioning
confidence: 99%
“…The AWCC was tested and used in different applications by many authors [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The AWCC was compared with other neutron coincidence detectors to investigate its precision, counting rate, accuracy, penetrability, stability, and the effect of sample inhomogeneity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Menlove and Bosler [13] showed that the instrument could be used for the assay of a wide range of HEU samples in form of stacked disks to simulate buttons and thin metal plates both in thermal and fast modes taking into consideration the neutron self-shielding and multiplication. The AWCC was also calibrated [14] for the assay of 93%-enriched fuel materials in different categories. Evaluation of the AWCC for field tests was performed by Krick and Rinard [15].…”
Section: Introductionmentioning
confidence: 99%